A study on the size effect of RC beam–column connections under cyclic loading. (15th July 2015) - Barbhuiya, Salim; Choudhury, Abdul Munim
Highlights: Performance of beam–column connections with three possible deficiencies. Energy dissipation of specimens indicated the existence of size effect. Size effect is more pronounced in specimens exhibiting brittle mode of failure. Abstract: Beam–column connection is one of the vital sub-assemblages of a structural system. This is mainly because their behaviour during earthquake is very critical. Hence, in the present study, an experimental programme was undertaken by considering three types of beam–column connections with some specific deficiencies. For each type, three different sizes of specimens were considered to evaluate the existence of size effect in beam–column connections. Cyclic load was applied using servo hydraulic dynamic actuators with displacement-controlled load of frequency of 0.025 Hz. Amplitudes of the displacement histories were scaled down for two-third and one-third models. It was observed that the size effect became more pronounced with the increase in the brittleness of the specimens. To compare the energy dissipation of specimens having different sizes of beam–column joints, a parameter energy dissipation per unit volume of joint ( eN ) was introduced. This parameter was correlated with different drift angles for different sizes of the specimen and accordingly variation of eN with drift angle for different sizes of specimens were plotted. The variation of stress with relative deflection was also correlated with size of the specimens. It was observed that energy dissipation of specimens per unit volume as well as the variation of stress with relative deflection indicated the existence of size effect.